Le larynx du phoque de Weddell (Leptonychotes weddelli, Lesson, 1826) - Piérard, Jean (Canadian Journal of Zoology, 1969)
A descriptive and functional study of cartilages, muscles, and cavities of the Weddell seal larynx is made.Several conclusions can be drawn from this study, (a) The glottis is, more than in other pinnipeds, better adapted toward protective closure of the larynx, (b) The membranous part of the vocal fold is in such position that it contributes little or not to sound production, (c) However, short howls may be produced at the level of the glottis, mainly of its intercartilaginous part, (d) It is suggested that trilling sounds are made at the level of the cricotracheal junction and that the rostral part of the trachea acts as a resonating chamber for these sounds.